Peningkatan Pengetahuan Pola Hidup Bersih dan Sehat serta Penggunaan Vitamin pada Anak di Panti Asuhan Claresta - Nasri Nasri; Vera Estefania Kaban; Hariyadi Dharmawan Syahputra; Junius Gian Ginting; Chyntia Glori Tania (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Achieving a healthy lifestyle requires a series of consistent steps, such as regular exercise, eating healthy and nutritious foods, getting enough rest, implementing a clean and healthy lifestyle, and consuming vitamins to boost external immunity. There is also concern about improving the health of children and adolescents, especially children who may have a minimal immune system that needs to be strengthened. The purpose of this activity is to provide education and counseling on how to live a clean and healthy lifestyle and to provide knowledge to children about the use of vitamins. The method of this activity is that children are first given questions for a pre-test about a clean and healthy lifestyle and vitamins, then present the material and close it with a post-test. As a result, only 8,57% of the students knew what a healthy lifestyle and vitamins were at the time of the pre-test. After the presentation of the material, the increase in children's knowledge increased by an average of 86,1%. The activity's conclusion is that it can teach children about living a healthy lifestyle and consuming vitamins. .